Species Identification of Bovine Bone Marrow from Nonbovine Products Using Multiplex PCR Technology - Yize Guan; Nan Li; Liyuan Sun; Ming-Cheng Li; Tancheng Li (Journal of Food Quality)
Bovine bone marrow is traditionally regarded as a highly nutritious food that has been widely used as a medicinal and health food for several decades in China. A large number of adulterated and counterfeit bone marrows from pigs and donkeys have been used in place of bovine bone marrow in commercial products, which are almost identical morphologically between species. Therefore, we explored the feasibility of multiplex PCR technology to differentiate bovine bone marrows from different domestic animals. Three pairs of specific primers for bovine, pig, and donkey were designed according to the conserved sequence in mitochondrial cytochrome b. A modified method was used to extract the genomic DNA from common domestic animals’ bone marrows. The optimal reaction conditions for triple PCR were optimized. A three-fold PCR detection assay was successfully established to identify three species of bovine, pig, and donkey. Three primers have good specificity and high sensitivity. Additionally, the assay sensitivity test confirmed that the extracted DNA concentration was the lowest in bovine bone marrow at 10°pg/μL. The assay also showed 100% specificity. Rapid authentication of bovine bone marrow and differentiation from nonbovine products can be achieved using an improved SDS alkali denaturation method and species-specific PCR assay. Both species-specific PCR methods described in this study can be potentially applied for the quality evaluation of functional food and drug resources.